Cytochrome b5 reductase deficiency and hereditary methemoglobinemia - Reading, Scott (Henry Stewart Talks, 2018)
Formation of methemoglobinemia, Review of methemoglobinemias types, Cytochrome b5 reductase (Cytb5 R), Mutations and clinical phenotypes of Cytb5 R deficiency, Differential diagnosis from other methemoglobinemias, Therapy of methemoglobinemia